Lanthanum, Gallium and their Impact on Oxidative Stress - Todorov, Lozan; Kostova, Irena; Traykova, Maria (Current Medicinal Chemistry, 2019)
The role metals play in living organisms is well established and subject to extensive research. Some of them participate in electron-exchange reactions. Such reactions cause generation of free radicals that can adversely impact biological systems, as a result of oxidative stress. The impact of ‘non-biological’ metals on oxidative stress is also a worthy pursuit due to the crucial role they play in modern civilization. Lanthanides (Ln) are widely used in modern technology. As a result, human exposure to them is increasing. They have a number of established medical applications and are being extensively researched for their potential antiviral, anticancer and anti-inflammatory properties. The present review focuses on lanthanum (La) and its impact on oxidative stress. Another metal, widely used in modern high-tech is gallium (Ga). In some respects, it shows certain similarities to La, therefore it is a subject of the present review as well. Both metals exhibit ionic mimicry which allows them to specifically target malignant cells, initiating apoptosis that makes their simple salts and coordination complexes promising candidates for future anticancer agents.
Keywords: Lanthanum